In-Hospital Outcomes of Acute Inferior Myocardial Infarction Associated with Complete Heart Block: A Coronary Care Unit Experience - Kabir, Ahmed Imran; Alam, Mohammad Ashraful; Rahman, Mohammed Mirazur; Musa, Manzurul Ibrahim (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Complete heart block (CHB) is a common complication in patients of acute inferior myocardial infarction (MI). Their in-hospital outcomes depend on the time of onset of the sequelae,pattern of newer area of infarction and concomitant complications. Objective: To see in-hospital outcomes of the patients with acute inferior myocardial infarction complicated by complete heart block. Methods: This prospective observational study was conducted in the Coronary Care Unit (CCU) under Department of Cardiology, Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh, between November 2014 and May 2015.A total of 100 patients (77 males and 23 females) were selected based on specific inclusion and exclusion criteria by using convenient sampling technique. All studyparticipants were evaluated by detailed history, clinical examination and relevant investigations.Response to different treatment modalities and their complications were recorded. Recovery of CHB was also monitored. Results: Mean age of the patients was 57.16±10.24 years.Early presentation (within 24 hours) of CHB had only 4.17% mortality. However, mortality increased in patients as CHB developed after 24 hours (26%). Overall, 10% mortality was evident despite advanced cardiac support.Complications reported in optimum medical treatment included hypotension (17 patients), bleeding (1 patient) and arrythmia (1 patient). 11% of the patients received temporary pacemaker by femoral vein approach.However, only 1 patient had hematoma, 1 had A-V fistula and 1developed vesovagal shock during puncture of the femoral vein. Duration of hospital stay was more forthe patients who were refractory to conservative medical treatment and received temporary pacemaker; however, the difference was not statistically significant (5.06±0.71vs.8.07±1.01; P>0.05). Conclusion:Complete heart block associated with acute inferior MI is very much responsive to optimum medical treatment and an early presentation of complete heart blockallows an early intervention, better prognosis and recovery. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 69-73